WACANA PENCERAHAN PERAN GENDER PADA PROGRAM SIARAN RADIO KOSMONITA DI SURABAYA - Andik Yuliyanto, ; Mukhzamilah, (Lentera, Jurnal Studi Perempuan, 2008)
Abstract This  articles  is  based  on  a  study  that  aims  at  revealing  the  roles,  topics, and  discourse  and  its  meaning  in  the  programs  broadcasted  by  Kosmonita Radio  Station  in  Surabaya.  The  selected  programs  were  Women  Global  News, Lipstik, Insert, and Obrolan Perempuan (Womens Talk). The study employed the discourse  analysis  model  proposed  by  M.A.K.  Halliday,  which  involved  ﬁeld, people involved, and mode. The  study  reveals  that  the  studied  radio  programs  by  Kosmonita  Radio Station  contained  topics  that  were  either  enlightening  or  empowering  women. Those   programs   provided   perspectives,   vision,   suggestions,   and   problem solution.  The  commonly-discussed  topics  were  womens  rights  in  reproductive health, marriage, interaction in public space, and equal treatment in workspace, from local to international scope, ranging from womens condition in Surabaya to that around the world. The language style that was used in Women Global News was scientiﬁcally argumentative, accompanied with data to support the opinions. In the program. Some   English   terms   were   used   and   required   conceptual   comprehension. Meanwhile, more informal programs like Lipstik, Obrolan Perempuan, and Insert used  more  informal  language  style,  without  necessarily  losing  their  purposes of  enlightening  and  empowering  women.  Particularly  in  Obrolan  Perempuan, some familiar proverbs were also discussed and given criticism for their gender- biased messages.